ANALISIS LIFE CYCLCE STRUKTUR MAIN LANDING GEAR UAV DENGAN MATERIAL ALUMINIUM BERDASARKAN VARIASI KECEPATAN LANDING - Ajie Erlangga Antariksa; Budi Aji Warsiyanto; Syarifah Fairuza (Jurnal Teknologi Kedirgantaraan, 2024)
Main landing gear is a component in UAVs that have support abilities to take offand landing. Repeated loads occur during UAV landings, impact of these cyclic loads can leadto fatigue failure in the main landing gear. The life cycle analysis aims to determine the lifespanof the main landing gear based on the influence of material variations and landing speedvariations. The materials considered are Al 6061 T6, Al 2024 T3, and Al 7075 T6, with landingspeed variations of 4 m/s, 6 m/s, 8 m/s, and 10 m/s. In this research, dynamic loading analysisand cyclic load analysis were performed on the UAV's main landing gear, modeled in the formof a leaf spring. Numerical analysis was conducted using finite element-based software. In thedynamic loading analysis results for landing speed variations, a speed of 4 m/s yielded amaximum stress value of 236,1 MPa and a maximum displacement of 2,949 mm, while aspeed of 10 m/s resulted in a maximum stress value of 308,8 MPa and a maximumdisplacement of 6,482 mm. In the dynamic loading analysis with material variations, thematerial Al 2024 T3 exhibited a maximum stress value of 362,6 MPa and a maximumdisplacement of 4,938 mm. In the cyclic load analysis, Al 6061 T6 had a minimum fatigue lifeof 659.060 cycles at a speed of 4 m/s and 6.786,6 cycles at a speed of 10 m/s. Al 2024 T3showed a minimum fatigue life of 3.308.100 cycles at a speed of 4 m/s and 16.739 cycles ata speed of 10 m/s. Al 7075 T6 had a minimum fatigue life of 982.900 cycles at a speed of 4m/s and 8.795,9 cycles at a speed of 10 m/s.